ANALISIS PENILAIAN PROPERTI KOMERSIAL (Studi Kasus : Villatel dan Condotel X, Kabupaten Bogor): (Studi Kasus : Villatel dan Condotel X, Kabupaten Bogor) - Tegar Wibowo; Ida Ayu Ari Anggreni (Politeknik Negeri Jakarta, 2021)
The economic development of Indonesia from year to year, especially in terms of tourism developments and also the supporting factors that are Condotel, Villatel, and other lodging places. Given the promising business opportunity in terms of commercial properties in the field of tourism support, thus causing a large number of entrepreneurs who intend to build the commercial property, but before building a commercial property required the proper calculation and estimate of funds, the estimate of the market price and also the time period of sales estimates on the future commercial property will be sold, where the value of this market is also used by a Bank in determining the amount of funds that can be approved if there is a commercial On the basis of this research will examine the market value and the value of the liquidation of commercial properties, especially on the commercial properties of Villatel and Condotel using the method of income approach and cost approach. The results of research obtained after the thorough calculation of Condotel and Villatel obtained the market value of Rp. 145 950 000 000, while the value of liquidation or forced selling value of Rp. 102 165 000 000. The liquidation value is less than the market value due to the value of liquidation is 70% of the nominal market value.